Integrasi Nilai Ethnoteologi Sebagai Strategi Penguatan Identitas Budaya dan Karakter Religius Peserta Didik di Lembaga Pendidikan Islam - Else Meina; Titi Oktarina Sambadha; Indah Wigati; Yuniar Yuniar (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This research examines the integration of ethnotheological values in Islamic education as a strategy to strengthen the cultural and religious identity of students, particularly within madrasahs. The study employs a qualitative approach using a literature review method to analyze various scientific sources related to ethnotheology, Islamic education, cultural integration, and the reinforcement of students’ religious identity. The findings indicate that ethnotheology, as a framework of culture-based theological reflection, is capable of connecting religious teachings with local traditions through curriculum development, learning activities, and the creation of an inclusive school culture. This integration not only enhances students’ religious understanding but also fosters pride in local culture, develops tolerant attitudes, and shapes adaptive characters capable of facing globalization without losing their religious and cultural roots. The implications of this ethnotheological integration are reflected in the strengthening of students' religious identity, the enhancement of pride in local culture, and the formation of a tolerant and multicultural character.